(untitled) (gjstudies, 2025)
This paper introduces a novel, multi-dimensional framework for conceptualizing and measuringfinancial reporting complexity (FRC) and investigates its non-linear influence on audit effort.Moving beyond traditional proxies such as firm size or industry, we define FRC as an emergentproperty arising from the interaction of structural, informational, and relational dimensionswithin a firm’s reporting ecosystem. The structural dimension captures the intricacy of organizational hierarchies and transaction networks; the informational dimension addresses thevolume, heterogeneity, and interconnectedness of accounting data; and the relational dimensionconsiders the strategic interactions and information asymmetry between management, auditors, and regulators. We propose that the relationship between FRC and audit effort is notmonotonic but follows an inverted U-shape, moderated by the deployment of advanced audittechnologies. At low to moderate levels of complexity, increased FRC demands greater auditorlabor and scrutiny. However, beyond a critical threshold, excessive complexity triggers a technological adaptation response, where auditors increasingly rely on and invest in sophisticateddata analytics, process mining, and AI-assisted continuous auditing tools, which can paradoxically streamline certain audit procedures while intensifying others related to model validationand interpretability. To test this hypothesis, we develop a composite FRC index using a combination of disclosed financial note metrics, textual analysis of annual reports, and networkanalysis of related-party disclosures. Empirical analysis, utilizing a hand-collected dataset froma diverse sample of publicly traded firms, supports the curvilinear relationship and identifies themoderating role of audit firm technology investment. Our findings challenge linear cost modelsin audit pricing and provide a nuanced understanding of how modern audit practices evolvein response to the growing intricacy of financial information environments. This research contributes to auditing literature by offering a more granular, systems-theoretic view of complexityand its implications for audit labor economics and technological adoption.